NEGATIVE PORTRAYAL OF POWERFUL WOMAN REFLECTED BY RAVENNA CHARACTER IN SNOW WHITE AND THE HUNTSMAN - HERNOMO, ANASTASIA CLAUDIA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Woman, Patriarchy, Snow White and The Huntsman Literature is written or spoken material that contains art. Literature is commonly used to refer to prose, novels, poetry, drama, short story, folktales, etc. Folktale is a term for various kinds of narrative prose literature found in the oral traditions of the world. Some folktales may pass in and out of written literature, and some stories of literary origin may cross over into oral tradition from one generation to other generation.  Nowadays, there are folktales that are written and also filmed.Film is one of the media that is made to visualize literary works that convey message to people. There are some films that are adapted from folktale, such as; Hansel and Gretel, Mirror Mirror, Enchanted, Sydney White and many others.In 2012, there was a movie adapted from Snow White story, Snow White and The Huntsman. Snow White and the Huntsman tells about Snow White whose stepmother, Ravenna, tried to get immortal life after taking over the kingdom from her husband, King Magnus. The writer analyze the misapplication of woman's power which is reflected by Ravenna character. To analyze Ravenna who reflects a strong, raise, and struggle to get higher position the writer use feminism approach. Dialogue and mise-en-scene also helps the writer to analyze Ravenna's act in the film.From the analysis, known that Ravenna reflects woman who is smart, independent, and powerful that is described as a woman who has bad deed and traits. Unfortunately, Ravenna lose from Snow White who represents woman who is dependent on man.The writer wants to give suggestion to the next researcher. The next researcher need to conduct further research on the analysis reveals the important things in it, because this film can still be analyzed using the other theory, such as semiotics. This film will be interesting to analyze the signs and symbols that appeared using semiotics theory. The other possibiltiy for the next researcher is analyze the other character using same theory, feminism.